Предмет: Математика, автор: 1213234

Самостійна робота
по математике

Приложения:

Ответы

Автор ответа: fenix6810
0

Ответ:

Пошаговое объяснение:

Bx=2Cx-Ax=2*(-2)-(-10)=-4+10=6

By=2Cy-Ay=2*(-4)-6=-14

Bz=2Cz-Az=2*(-5)-(-3)=-10+3=-7

B(6;-14;-7)

2) AB=(-4-(-3);-5-5;-8-8)=(-1;-10;-16)

|AB|=√((-1)²+(-10)²+(-16)²)=√(1+100+256)=√357

A+B=(-7;0;0)

A-B=(1;10;16)

AB=(-3)*(-4)+(5)*(-5)+8*(-8)=12-25-64=-77

cos(AB)=-77/(√98*√105)=-77/√(49*2*21*5)=-11/√210

|A|=√((-3)²+5²+8²)=√(9+25+64)=√98

|B|= √((-4)²+(-5)²+8²)=√(16+25+64)=√105

Похожие вопросы
Предмет: Математика, автор: zlatakuhal
Предмет: Алгебра, автор: maksimlackij7
Предмет: Математика, автор: routinesevendays